New pathways for the synthesis of indolyl-containing quinazoline trifluoroacetohydrazides - Yu. A. Azev; O. S. Koptyaeva; O. S. Eltsov; Yu. A. Yakovleva; T. A. Pospelova (Chimica Techno Acta)
The reactions of indole-3-carbaldehyde arylhydrazones with quinazoline in TFA proceed at the 7' position of the aryl part of the hydrazone molecule to form σ-adducts of quinazoline trifluoroacetohydrazides.